2010
DOI: 10.1116/1.3449808
|View full text |Cite
|
Sign up to set email alerts
|

Improving the metallic content of focused electron beam-induced deposits by a scanning electron microscope integrated hydrogen-argon microplasma generator

Abstract: Articles you may be interested inPolymethyl methacrylate/hydrogen silsesquioxane bilayer resist electron beam lithography process for etching 25 nm wide magnetic wires J. Vac. Sci. Technol. B 32, 021601 (2014); 10.1116/1.4867753 Modular ultrahigh vacuum-compatible gas-injection system with an adjustable gas flow for focused particle beam-induced deposition Electrodes for carbon nanotube devices by focused electron beam induced deposition of gold Local coinjection of a ͑H 2 -Ar͒ microplasma jet and Cu͑O 2 C 5 F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 43 publications
1
26
1
Order By: Relevance
“…For the 15 μm long lines we used 100 µs dwell time per pixel, 0.5 nm pixel distance, and 300 line repetitions with a refreshment time of 3 s. The beam current was 1 nA, which corresponds to the dose of 9 nC/µm 2 and exposure time of 900 s. Tip deposits were obtained by the stationary dot exposure mode exposing a pixel for two minutes. Line and freestanding-rod deposits with (hfac)CuDMB and (hfac)CuVTMS from earlier FEBID experiments [39,40] were performed with a single scan at around 30 nm/s with 600 pA.…”
Section: Experimental Febidmentioning
confidence: 99%
“…For the 15 μm long lines we used 100 µs dwell time per pixel, 0.5 nm pixel distance, and 300 line repetitions with a refreshment time of 3 s. The beam current was 1 nA, which corresponds to the dose of 9 nC/µm 2 and exposure time of 900 s. Tip deposits were obtained by the stationary dot exposure mode exposing a pixel for two minutes. Line and freestanding-rod deposits with (hfac)CuDMB and (hfac)CuVTMS from earlier FEBID experiments [39,40] were performed with a single scan at around 30 nm/s with 600 pA.…”
Section: Experimental Febidmentioning
confidence: 99%
“…5 The second common problem is that the purity of the deposits is often low -the inter-actions with secondary electrons lead to incomplete separation of ligands. A number of purification techniques has been suggested to compensate for this effect-for example reductive by atomic hydrogen 6 or oxidative with electron impact stimulated water, 7 but making a pure deposit directly would be preferable. For iron pentacarbonyl it has been shown that under specific ultrahigh vacuum conditions the autocatalytic decomposition leads to the purity of up to 95%.…”
Section: Introductionmentioning
confidence: 99%
“…[46] However, in the FEBID process, nanostructures deposited from these precursors contain significant carbon contamination. [47,48] UHV surface science studies of precursors containing bidentate chelating ligands found that the electronsimulated reactions are comprised of two steps, as seen for precursors containing exclusively monodentate ligands. However, the chemical reactions for these more complex precursors are less well-defined than for precursors that only contain simple monodentate ligands.…”
Section: Monodentate Ligands: Heteroleptic Complexesmentioning
confidence: 97%